Official Discourse versus Indigenous Voices? Russian Narrative and Life Stories from the Siberian (Far) North - Samson Normand de Chambourg, Dominique (Translation Studies: Theory and Practice, 2023)
Due to its territorial expansion over the centuries, Russia has constantly incorporated the most diverse peoples and languages. At a time when the Federation wants to find a great national narrative, the authorities put forth the necessity “to protect historical truth” (Article 67.1 § 3 of the Constitution) to impose a memory policy, to the exclusion of all others. Thenceforth, the monopoly of the State on history, promoted by institutions of historical propaganda and passed on throughout society, condemns the silencing of the unedited memory of communities that do not have the same reading of past events. This is why, through a historical and anthropological approach based on old sources and the word collected in the tundra and taiga until 2019, the point will be to put into perspective the Russian national narrative, thanks to the reading of the minority indigenous peoples of (sub)Arctic Siberia.